Back Cover: Coke‐Tolerant Gadolinium‐Promoted HZSM‐5 Catalyst for Methanol Conversion into Hydrocarbons (ChemCatChem 9/2017). Issue 9 (10th May 2017) - Kim, Sungtak; Kim, Yong Tae; Hwang, Ahron; Jun, Ki‐Won; Kwak, Geunjae
Abstract : The Cover picture shows that carbon deposition and coke growth are inhibited by the gadolinium effect on the ZSM‐5 surface. In their Communication, S. Kim et al. explain a role and nature of gadolinium as a coke inhibitor when it applied the ZSM‐5 catalyst for methanol‐to‐hydrocarbon reaction. Gadolinium oxide thin films covered the ZSM‐5 crystals, and gadolinium atoms uniformly dispersed on the surface enhanced the basicity of the parent ZSM‐5. These synergetic effects improve durability of the acidic function and diminish growth of coke precursors, resulting in an increased catalyst lifetime. More information can be found in the Communication by S. Kim et al. onpage 1567 in Issue 9, 2017 (DOI:10.1002/cctc.201601559 ).